2021
DOI: 10.1007/s12517-021-07149-5
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations, spatial distribution, and human health risk assessment of asbestos fibers in ambient air of Tehran, Iran

Abstract: The aim of current research was to determine airborne asbestos fiber concentrations in the ambient air of Tehran, and to investigate their spatial distribution, seasonal variation, and human health risk assessment. For this, the sampling of the study was carried out during August 2017 and June 2018, and totally, 64 samples were taken from 8 stations along the different areas of Tehran. The concentrations of airborne asbestos fibers were determined by phase contrast microscope (PCM) and scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Numerous studies showed comparable positive and negative relationships between a few meteorological parameters and the amount of asbestos fibers in the air of the studied cities; an increase in wind speed is positively correlated with the amount of asbestos fibers in the air, whereas an increase in temperature, relative humidity, and air pressure shows a negative correlation [ 55 ]. Ghorbani et al investigated traffic and urban transportation as the most important factors in the dispersion of asbestos fibers into the air of Isfahan, which is consistent with the results of asbestos fibers dispersion map for the air of the city studied in the current research [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies showed comparable positive and negative relationships between a few meteorological parameters and the amount of asbestos fibers in the air of the studied cities; an increase in wind speed is positively correlated with the amount of asbestos fibers in the air, whereas an increase in temperature, relative humidity, and air pressure shows a negative correlation [ 55 ]. Ghorbani et al investigated traffic and urban transportation as the most important factors in the dispersion of asbestos fibers into the air of Isfahan, which is consistent with the results of asbestos fibers dispersion map for the air of the city studied in the current research [ 54 ].…”
Section: Resultsmentioning
confidence: 99%